Reconsidering teachers' basic psychological needs in relation to psychological functioning across an academic year. (March 2023) - Corbin, Catherine M.; Downer, Jason T.; Lowenstein, Amy E.; Brown, Joshua L.
Abstract: Understanding psychological processes underlying change in teachers' psychological functioning is crucial to identifying the developmental processes at play. Guided by self-determination theory, this study uses a sample of 330 teachers in the northeastern United States of America to examine if initial levels of teachers' basic psychological needs (i.e., global psychological need satisfaction, autonomy, competence, relatedness) are associated with change in components of psychological functioning over time. Results indicate that most psychological needs are unassociated with change in psychological functioning, raising questions about how and when those needs are implicated to support teachers. Implications for research and practice are discussed. Highlights: A novel operationalization of basic psychological needs was examined related to change in teachers' well-being. Global psychological need satisfaction was negatively associated with negative affect over one academic year. Autonomy was positively associated personal accomplishment over one academic year. No other significant associations emerged, raising questions about psychological needs related to change in well-being. Repeated measures designs can further illuminate teachers' basic psychological needs related to change well-being.